Making Decarbonization Work for Workers: Policies for a just transition to a zero-carbon economy - Mertins-Kirkwood, Hadrian (Author) (Canadian Centre for Policy Alternatives; Adapting Canadian Work and Workplaces to Climate Change, 2018)
In light of the federal government’s pledge to launch a Task Force on Just Transition in 2018, this report makes a unique contribution by using census data to identify the regions in each province with the greatest reliance on fossil fuel jobs. While fossil fuel dependence is overwhelmingly concentrated in Alberta, with a few “hot spots” in Saskatchewan and British Columbia, the report identifies communities from other provinces where fossil fuel jobs represent a significant part of the local economy – for example, Bay Roberts, Newfoundland; Cape Breton, Nova Scotia; Saint John, New Brunswick; Sarnia, Ontario. The report also makes the useful distinction between “reactive” just transition policies, which are intended to minimize the harm to workers of decarbonization, and “pro-active” just transition policies, which are intended to maximize the benefits.